2002
DOI: 10.3346/jkms.2002.17.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and Molecular Genetic Study of MELAS and MERRF in Korean Patients

Abstract: Mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episode (MELAS) and myoclonic epilepsy and ragged-red fibers (MERRF) are rare disorders caused by point mutation of the tRNA gene of the mitochondrial genome. To understand the pathogenetic mechanism of MELAS and MERRF, we studied four patients. Serially sectioned frozen muscle specimens with a battery of histochemical stains were reviewed under light microscope and ultrastructural changes were observed under electron microscope. The polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Therefore, selection of the affected organ or tissues with heavy mutation loads is also important in increasing the detection sensitivity. Southern blotting is another method that can increase the sensitivity in low mutant‐loaded individuals 9,10. Despite all of these limitations, we found that the A3243G and A8344G mutations are the most common mtDNA mutations in Korea, which can be used as a guide to efficiently screen mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, selection of the affected organ or tissues with heavy mutation loads is also important in increasing the detection sensitivity. Southern blotting is another method that can increase the sensitivity in low mutant‐loaded individuals 9,10. Despite all of these limitations, we found that the A3243G and A8344G mutations are the most common mtDNA mutations in Korea, which can be used as a guide to efficiently screen mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Among the reported mutations, A3243G and A8344G are the most common pathogenic mutations of mtDNA. They are genetically and phenotypically distinct 9,10. The A3243G mutation was originally described in a patient with MELAS, which is clinically characterized by recurrent stroke‐like episodes, migraine, nausea, and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…1A). 19,20) It is a muscle fiber in which compensatory proliferation of dysfunctional mitochondria accumulates in subsarcolemmal and intermyofibrillar space. The bright red masses around the sides of the muscle fiber contrasts with green sarcoplasm just as the name describes.…”
Section: Skeletal Muscle Biopsy In Mitochondrial Myopathymentioning
confidence: 99%
“…RRFs , ragged blue fibers, and COXnegative fibers may or may not coincide. 19) Other frequent histologic findings of mitochondrial myopathies include typespecific muscle fiber atrophy and fibers with lipid or glycogen accumulation. Electron microscopy reveals mito chondrial proliferation in subsarcolemmal or intermyofibrillar space.…”
Section: Skeletal Muscle Biopsy In Mitochondrial Myopathymentioning
confidence: 99%
See 1 more Smart Citation